2020
DOI: 10.1021/acsami.9b20505
|View full text |Cite
|
Sign up to set email alerts
|

Study on Ca Segregation toward an Epitaxial Interface between Bismuth Ferrite and Strontium Titanate

Abstract: Segregation is a crucial phenomenon, which has to be considered in functional material design. Segregation processes in perovskite oxides have been the subject of ongoing scientific interest, since they can lead to a modification of properties and a loss of functionality. Many studies in oxide thin films have focused on segregation toward the surface using a variety of surface-sensitive analysis techniques. In contrast, here we report a Ca segregation toward an in-plane compressively strained heterostructure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The formation of O vacancies has a lower expected Ca ratio but can be considered a more likely case due to our previous results. 61 Nonetheless, at the growth temperature of the film of 700 °C, according to the DFT simulations about 50 times more Ca is expected in BFO than in BO. With increasing temperature, the ratio becomes in general smaller.…”
Section: Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The formation of O vacancies has a lower expected Ca ratio but can be considered a more likely case due to our previous results. 61 Nonetheless, at the growth temperature of the film of 700 °C, according to the DFT simulations about 50 times more Ca is expected in BFO than in BO. With increasing temperature, the ratio becomes in general smaller.…”
Section: Results and Discussionmentioning
confidence: 89%
“…The film structure was investigated in the [010] c cross-sectional orientation concerning the cubic STO substrate, which also complies with the [010] pc (pseudocubic) zone axis of bismuth ferrite. 61 The HAADF image in Figure 1 a shows a cross-section of the Ca- and Co-doped BiFeO 3 film (BCFCO) and the interface with the STO substrate in the bottom part. In the film, approximately 5 nm away from the interface, white stripes with a width of approximately one unit cell appear running in the [100] direction.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These received cells are utilized to determine the absolute intensity from the unfiltered image by integrating over a defined area corresponding to each atomic column. Columns at the edge of the image that lie not entirely in it are excluded. , The integrated column intensity is a robust measurement, as it is insensitive to the probe shape and the defocus. , The second MatLab script was written to evaluate (i) the fitted atomic-column positions from the first script according to the spacings between the atomic sites, (ii) the polarization due to shifts of the central Fe atom, and (iii) to visualize the data. The EELS spectra were processed using the built-in functions of digital micrograph and additionally filtered in OriginPro 2016 using a Savitzky–Golay filter with a window of nine data points for denoising.…”
Section: Methodsmentioning
confidence: 99%
“…Ca doping in BiFeO 3 can induce oxygen vacancies because the replacement of Bi 3+ with Ca, which is an alkaline earth metal and therefore cannot have a higher oxidation state than 2+, has a hole doping effect. Stoichiometrically Ca doping in Bi 1– x Ca x FeO 3−δ would lead to δ = x /2 oxygen vacancies. It has been reported that for doping ratios of x ≥ 0.2, the oxygen vacancies arrange in ordered superstructures. , Thereby, Ca is not uniformly distributed but can segregate to the energetically most favorable position. ,, When relatively thick films are under a compressive (tensile) strain, these superstructures are expected to be arranged parallel (perpendicular) to the interface, as shown in a study for LaCoO 3– x films . For thin, tensile-strained films where the surface energy becomes dominant compared to the bulk energy, the effect is seen, in order to minimize the surface energy, the perpendicular arranged oxygen defects become parallel .…”
Section: Introductionmentioning
confidence: 99%